What names did the Anti-nicenes use for Catholics and Arians? - Moorhead, John (Augustinianum, 2010)
The parties involved in the Trinitarian disputes that led to and followed the Council of Nicaea are generally referred to as Catholics and Arians. But such terminology reproduces that of the party that was ultimately victorious, and this paper utilizes the evidence of Latin texts from the fourth to the sixth centuries to enquire into the language used by the other side. It will draw attention to the use of such terms as Homousians and Romans for those better known as Catholics, and the application of such general concepts as lex and religio.